GEOLOGICAL MEDIUM AND UNDERGROUND HYDROSPHERE - S. V. Alekseev; Е. А. Kozyreva (Геодинамика и тектонофизика, 2015)
The article informs about the history, the staff, researches and scientific activities of the Laboratory of Hydrogeology and the Laboratory of Engineering Geology and Geoecology of the Institute of the Earth’s Crust, SB RAS. It reviews the major results of scientific research projects implemented from 2009 to 2013, which provided for determination of characteristics of the geological medium and hydrosphere of East Siberia and Mongolia in natural and technogenic conditions and modeling of the evolution of natural, natural-technogenic hydrogeological and engineering geological systems in regions with contrasting climate conditions and specific geological settings.